Offshore Wind Energy as A Pivotal Factor in Recovery, Resilience and Sustainability – Status Quo And Lessons Learned from Selected Countries in Europe - Vlatka BILAS; Lana TRIFUNIC (Communications of International Proceedings, 2022)
Offshore wind energy has been identified as a pivotal factor in recovery, resilience and sustainability, which has been clearly shown by the very focused and detailed strategic efforts and well defined legal framework for achieving sustainable development, climate neutrality and low-carbon economy globally, especially in the EU. Its strategic vision and regulatory efforts have positioned Europe as the world's leading offshore energy producer. Through secondary research methods and qualitative analysis, the aim of the analysis is to identify and compare Belgium’s, Netherlands’ and Poland’s strategic efforts and concrete and practical activities in offshore wind energy, since they have similar sectoral characteristics - great potential for the development of offshore wind farms, defined regulatory framework and established stable practices for offshore wind exploitation. The analysis has shown differences in their experience level and similarities in their long-term vision and goals in the offshore wind energy sector, as well as their targeted actions for evolving in order to achieve resilience and sustainability, and to contribute to establishing climate neutrality and low-carbon economy.
Keywords: renewable offshore wind energy sector in Europe; sustainable development and climate neutrality; low-carbon economy; recovery and resilience